Daptomycin for the treatment of bacteraemia due to vancomycin-resistant enterococci (2014)
Treatment of severe infections caused by vancomycin-resistant enterococci (VRE) is challenging due to the scarcity of reliable therapeutic alternatives.Inthis context,daptomycin(DAP), a lipopeptide antibiotic, has emerged as an interesting alternative as itis one ofthe few compounds that retain in vitro bactericidal activity against VRE isolates, although it has not been approved for this purpose by regulatory agencies. In this review, we will summarise the clinical, animal and in vitro evidence evaluating the efficacy of DAP for the management of deep-seated VRE infections. In addition, we will address important clinical concerns such as the emergence of DAP resistance during therapy and reports of therapeutic failure with DAP monotherapy. Finally, we will discuss possible future strategies (such as the use of higher doses and/or combination therapies) to optimise the use of this antibiotic against VRE.